Reflections on the Pragmatics of the Illustrated Perspective Treatise: Performative Failures and (Pre-) Romantic Innovations - Ralickas, Eduardo (Intermédialités / Intermediality)

(untitled) (Revue Intermédialités (Presses de l’Université de Montréal), 2010)
This essay reconsiders visual demonstrations contained in a selection of illustrated perspective treatises. Based on a fundamental distinction made in the field of pragmatics, the author argues that the images designed to demonstrate/teach/instantiate the perspectival system are plagued by a contradiction between the conceptual “content” of perspective and the figurative means deployed to display such content. In all cases, this aporia, which defines the teaching of perspective by means of images, arises when the figurative discourse of perspective attempts to integrate a representation of its user within the system itself. In closing, the author suggests that the perspective treatise’s “pragmatic unconscious” allows one to shed new light on the pictorial innovations of German romanticism, particularly in the work of Caspar David Friedrich, which is tied to fundamental (and hitherto unforeseen) ways to the “failures” of the classical age.